PRECARIZAÇÃO DO TRABALHO E SUAS PARTICULARIDADES NO TRABALHO DOCENTE DA REDE ESTADUAL DE EDUCAÇÃO BÁSICA DO ESTADO DO PARANÁ A PARTIR DA REFORMA DO ESTADO BRASILEIRO NA DÉCADA DE 1990 - NOMINATO, JEAN CLAUDIO SALES (2022)
The general objective of this bibliographical work was to analyze the precariousness of the teaching work in the public school system of the State of Paraná since the reform of the Brazilian State in the 1990s. Considering that precarization is multifactorial and is related not only to public/educational policies, but also to economic and ideological factors, the historical-dialectical materialist method was used based on its ontological conception and its categories of historicity and social totality. Initially, the foundations of the precariousness phenomenon were verified, its link to the capitalist production mode until its arrival in the public department through the reform of the Brazilian State and neoliberal policies. The ideological influence of international organizations in the precariousness of the teaching work and the main public policies that deal with the teaching work in Brazil were pointed out. Then, the precarious teaching work in Paraná was analyzed by examining the educational policies, making the counterpoint between the effective teachers and the temporary ones in the question of rights. The main educational policies that impacted the work of teachers during the Lerner, Requião, and Richa administrations were selected, as well as the intensification of the work of teachers in the state public network during the covid-19 pandemic in the Ratinho Junior administration. It was observed how, through these policies, the precarious situation of teachers in the state of Paraná was amplified and legitimized. From the reflections made, it is concluded that, although public policies do not solve the issue of precarization and the exploitation of labor by capital, teachers, as well as workers in general, need to have the minimum conditions for survival and better working conditions and salaries. The ontological link between labor precariousness and the capitalist mode of production cannot be lost sight of, because this allows us to glimpse and achieve a fairer society, one that overcomes class divisions as well as all kinds of human exploitation.